Analisa Sistem Informasi Centra Pelabuhan Indonesia - Dian Arisanti; Candra Bayu Suwito; Soedarmanto (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
The implementation of the Centra Information System has brought major changes to Indonesian Port management. This research is in the form of qualitative descriptive research with data collection methods carried out by means of observation, interviews and documentation. discusses the benefits, challenges, and suggestions for optimizing the use of these modules. Centra increases operational efficiency by automating business processes and providing real-time data access. However, implementation is often faced with integration complexity, unexpected costs, and excessive customization. Employee engagement and change management are critical to overcoming these barriers. The Finance and Accounting module allows management to make decisions based on accurate and up-to-date data, optimize financial management, and report company performance better. The Material Management module helps manage inventory, supply chain and project management more efficiently. The Human Capital Management (HCM) module supports decision making in human resource management. Employee management, performance and development become more effective, increasing productivity and employee satisfaction. Future suggestions include regular system maintenance, ongoing training, and improved integration. Performance evaluation and integration of the latest technology are also crucial. The success of Centra Information Systems depends on collaboration between departments, planning for future needs, and adapting to change. By overcoming these challenges and following these suggestions, companies can optimize Centra implementation and take full advantage of the Finance and Accounting, Material Management, and Human Capital Management (HCM) modules to achieve higher efficiency, productivity, and competitiveness.